Comparison of simulated cone beam computed tomography to conventional helical computed tomography for imaging of rhinosinusitis. (27th February 2014) - Fakhran, Saeed; Alhilali, Lea; Sreedher, Gayathri; Dohatcu, Andreea C.; Lee, Stella; Ferguson, Berrylin; Branstetter, Barton F.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Cone beam computed tomography (CBCT) has emerged as a low radiation dose alternative to traditional computed tomography (CT) to evaluate the paranasal sinuses. The purpose of our study was to determine how often clinically important findings would be missed if CBCT was used routinely for sinus imaging. Study Design Retrospective review. Methods We evaluated all maxillofacial CT scans performed for sinusitis over a 1‐year period. The original multidetector CT (MDCT) images were reviewed retrospectively. A theoretical CBCT was then created from the original study utilizing only the bone algorithm images and separately reviewed. We calculated the proportion of abnormal findings that were identified on the MDCT but would have been missed by the theoretical CBCT, and reviewed the medical record to determine which potentially missed findings would have changed management. Radiation dose from the MDCT scanners was calculated and compared to published dose estimates for the paranasal sinuses on CBCT. Results Maxillofacial CTs from 361 consecutive patients were included, of which 12 (3.3%) demonstrated findings that would have been missed on the theoretical CBCT. Of those, four (1.1%) would have resulted in a change in management. Effective radiation dose for our scanners ranged from 0.67 mSv to 2.15 mSv, compared to a published estimated dose of 0.2 mSV for CBCT. Conclusions In the majority of patients undergoing simulated CBCT for evaluation of sinusitis, incidental findings of soft‐tissue disease were rare. With appropriate selection of patients, CBCT can offer substantial radiation dose reduction and may provide a viable alternative to standard MDCT sinus imaging protocols. Level of Evidence 4 Laryngoscope, 124:2002–2006, 2014